Are the risks of treatment to cure a child with severe sickle cell disease too high?. (23rd November 2017) - de Montalembert, Mariane; Brousse, Valentine; Chakravorty, Subarna; Pagliuca, Antonio; Porter, John; Telfer, Paul; Vora, Ajay; Rees, David C
Abstract : Haematopoietic stem cell transplantation from alternative donors is curative for children with sickle cell disease, but risk of death is high. David Rees and colleagues call for greater caution in its use